2000
DOI: 10.1103/physrevlett.84.1070
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Kinks: Nucleation, Diffusion, and Annihilation

Abstract: We investigate the nucleation, annihilation, and dynamics of kinks in a classical (1+1)-dimensional φ 4 field theory at finite temperature. From large scale Langevin simulations, we establish that the nucleation rate is proportional to the square of the equilibrium density of kinks. We identify two annihilation time scales: one due to kink-antikink pair recombination after nucleation, the other from non-recombinant annihilation. We introduce a mesoscopic model of diffusing kinks based on "paired" and "survivor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
56
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…3 we have plotted S versus T for n = 1−6 domain walls using the parameter values in [4]. Choosing S nuc according to (13) we find excellent agreement with the numerical results. As also discussed in [4] we note that the switching scenario depends on T .…”
supporting
confidence: 59%
See 1 more Smart Citation
“…3 we have plotted S versus T for n = 1−6 domain walls using the parameter values in [4]. Choosing S nuc according to (13) we find excellent agreement with the numerical results. As also discussed in [4] we note that the switching scenario depends on T .…”
supporting
confidence: 59%
“…The Ginzburg-Landau equation in its deterministic form has been used both in the context of phase ordering kinetics [10] and in its complex form in the study of pattern formation [11]. In the noisy case for a finite system the equation has been studied in [12]; see also an analysis of the related φ 4 theory in [13]. In the present problem the noisy equation provides a generalization of the classical Kramers problem [14] to spatially extended systems.…”
mentioning
confidence: 99%
“…For more background on the non-noisy case in the contexts of zero-temperature Ising/Potts models and diffusion limited reactions, see [10,11,12]. The scaling limits for voter models, with or without noise, expressed in terms of Brownian webs with or without marks, should be the same scaling limits one gets for certain stochastic PDE models that arise in a variety of physical settings, e.g., those that describe nucleation, diffusion and annihilation of coherent structures (kinks) in a regime where they can be regarded as pointwise objects-see, e.g., [13] (also [14]) and references therein. This happens in the stochastic GinzburgLandau equation in the limit of small noise and large damping [15] or in a classical (1 + 1)-dimensional φ 4 field theory at finite (low) temperature [13].…”
Section: Introductionmentioning
confidence: 95%
“…It is simpler for the A + A problem because a number of appropriate non-chemical species can be identified that essentially undergo the simplest annihilation reaction or variants thereof. Examples include exciton annihilation experiments in one-dimensional pores and in effectively one-dimensional polymer wires [15], excited molecule naphthalene fusion and quenching experiments in one-dimensional pores [27], and kink-antikink simulations in one dimension [28]. Experimental observations of the A + B anomalies instead generally involve reaction fronts.…”
Section: Introductionmentioning
confidence: 99%